1987
DOI: 10.1002/jnr.490170411
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides fail to enhance behavioral recovery after bilateral ablation of the visual cortex

Abstract: Postsurgical injections of GM1 gangliosides (30 mg/kg IP) reduced neither behavioral deficits in rats following bilateral ablation of the visual cortex nor the extent of retrograde degeneration of neurons in the dorsolateral geniculate nucleus that typically accompanies large lesions of the visual cortex. Our findings are in contrast to previous research, in which ganglioside treatments have been shown to enhance the rate of functional recovery after lesions in other parts of the central nervous system. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This may be due to methodological differences -the use of a particular strain of rats (Johnson and Mitchell, 2003) and amount of time with access to the running wheels -both per day and in total. We used Wistar rats and 6 hours/day access to the running wheels for 1 week based on results showing elevation in plasticity-related proteins after the first week of voluntary running (Butler et al, 1987;Griesbach et al, 2004aGriesbach et al, , 2004bGriesbach et al, , 2008Griesbach et al, , 2009. Interestingly, in a study comparing different intensities of forced running, Shen et al (2013) reported that low intensity exercise led to a significant improvement in spatial memory after controlled cortical impact.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This may be due to methodological differences -the use of a particular strain of rats (Johnson and Mitchell, 2003) and amount of time with access to the running wheels -both per day and in total. We used Wistar rats and 6 hours/day access to the running wheels for 1 week based on results showing elevation in plasticity-related proteins after the first week of voluntary running (Butler et al, 1987;Griesbach et al, 2004aGriesbach et al, , 2004bGriesbach et al, , 2008Griesbach et al, , 2009. Interestingly, in a study comparing different intensities of forced running, Shen et al (2013) reported that low intensity exercise led to a significant improvement in spatial memory after controlled cortical impact.…”
Section: Discussionmentioning
confidence: 97%
“…The timing of a behavioural treatment is of crucial importance for successful outcome, but the number of preclinical studies investigating the topic is so far sparse. Whether to start early or later after injury appears to depend on severity of lesion, the nature of behavioural rehabilitative intervention, and the function to be recovered (Barbay et al, 2006;Biernaskie et al, 2004;Butler et al, 1987;Griesbach et al, 2004aGriesbach et al, , 2004bGriesbach et al, , 2007Malá et al, 2012;Shen et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation